A Genomewide Scan for Genetic Structure and Demographic History of Two Closely Related Species, Rhododendron dauricum and R. mucronulatum (Rhododendron, Ericaceae) - Yang, Baiming; Zhang, Guoli; Guo, Fengping; Wang, Manqi; Wang, Huaying; Xiao, Hongxing (Frontiers in Plant Science, 2020)
Understanding the processes of divergence and speciation is an important task for evolutionary research, and climate oscillations play a pivotal role. We estimated the genetic structure and demographic history of two closely related species of Rhododendron, R. dauricum and R. mucronulatum, distributed in northeastern China using 664,406 single nucleotide polymorphic loci of specific-locus amplified fragment sequencing (SLAF-seq) and 4 chloroplast DNA (cpDNA) fragments, sampling 376 individuals from 39 populations of these two species across their geographic distributions. The geographical distribution of cpDNA haplotypes revealed that R. dauricum and R. mucronulatum have different spatial genetic structures and haplotype diversity. Analysis of molecular variance (AMOVA) results showed that these two species have significant genetic differentiation and that the phylogeny demonstrates that these two species clustered a monophyletic group based on SLAF data, respectively, but not in cpDNA data. The evidence of significant gene flow was also detected from R. mucronulatum to R. dauricum. A deep divergence between the two species was observed and occurred during the early Oligocene. The niche models showed that the two species have different demographic histories. Thus, our results imply that geography and climate changes played important roles in the evolutionary process of R. dauricum and R. mucronulatum, and although there was an interspecific gene flow, the divergence was maintained by natural selection.